Utilization of Alurities Trisperma Oil as Biodiesel - Sari, Gustry Ratna; Satrio, M. Akbar; Mulyaningsih, Rizki; Irene, Imer Ayu; Paramita, Vita (Journal of Vocational Studies on Applied Research, 2020)
Biodiesel is one of the solutions to the many uses of fossil fuels. Biodiesel itself is a fuel derived from vegetable oil (plant or vegetable fat) called biofuel. In this study, biodiesel used is based on sunan candlenut. The purpose of this study was to determine the optimum time conditions (1.5; 2; 2.5 hours) and the comparison of solvents with candlenut (0.25; 0.2; 0.17) in the manufacture of candlenut oil, as well as knowing the process of making biodiesel. The method used is the manufacture of hazelnut oil by extraction using Soxhlet. The resulting oil was esterified using methanol with sulfuric acid catalyst at a reaction temperature of 60 0C for 60 minutes. The volume ratio between oil and methanol is 4: 1 followed by transesterification at 50 0C for 30 minutes. In the research, the results were optimum time and the number of solvents for good extraction at 2 hours and the ratio of solvents to hazelnut was 0.17. The resulting biodiesel density was 0.82 gr / ml, viscosity was 4.07Cp, FFA value was 1.4%, and the saponification rate was 274.4. From these data it can be said that the Biodiesel produced is approaching the Indonesian National Standard.